Correlation of Education Level with Mother's Knowledge About the Nutritional Status of Stunted Toddlers - Sitorus, Rotua Sumihar; Suprianto, Suprianto (Universitas Prima Indonesia, 2024)
Chronic malnutrition due to prolonged malnutrition resulting in stunted growth and development. Educated and knowledgeable mothers have a big influence on the pattern of regulating balanced food needs for the growth and development of toddlers. The research was directed at determining the correlation between educated and knowledgeable mothers on the nutritional status of stunted toddlers in the Namorambe Community Health Center work area. Quantitative descriptive research was conducted cross-sectionally. The population was 32 mothers who had stunted toddlers (0-59 months) and the total was the sample. Univariate and bivariate analyzes were carried out to describe the frequency distribution of respondents' characteristics and determine the correlation between educated and knowledgeable mothers regarding the nutritional status of stunted toddlers. The results showed that mothers ranged from 20-30 years old and had upper secondary education as many as 25 (78.1%) and 21 (65.6%); toddler age 37-60 months, male gender, stunted toddler, and poor maternal knowledge were 16 (50%), 17 (53.1%), 22 (68.8%) and 23 (71.9%); and as many as 21 (65.6%) and 12 (37.5%) respondents had high school education and poor knowledge; as well as the Chi-square analysis results of p-value = 0.038, respectively. In the research, there was a correlation between educated and knowledgeable mothers on the nutritional status of stunted toddlers in the Namorambe Community Health Center work area.